Estimating Daily Net Radiation over Vegetation Canopy through Remote Sensing and Climatic Data - Samani, Zohrab; Bawazir, A. Salim; Bleiweiss, Max; Skaggs, Rhonda; Tran, Vien D (Journal of irrigation and drainage engineering, 2007)
Net radiation ( Rn ) =key variable in hydrological studies. Measured net radiation data are rarely available and are often subject to error due to equipment calibration or failure. In addition, point measurements of net radiation do not represent the diversity of the regional net radiation values which are needed for large scale evapotranspiration mapping. A procedure has been developed to estimate daily net radiation using canopy temperature, albedo, short wave radiation and air temperature. This procedure makes it possible to estimate Rn by combining information from satellite and local weather stations. Three different methodologies are presented to estimate net radiation. Comparisons between net radiation using the three methods resulted in average error ranging from 1 to 30% and standard error of estimate ranging from 1.06 to 5.34 MJ∕ m2 ∕day .